2015
DOI: 10.1038/srep14669
|View full text |Cite
|
Sign up to set email alerts
|

Pre-amyloid oligomers of the proteotoxic RepA-WH1 prionoid assemble at the bacterial nucleoid

Abstract: Upon binding to short specific dsDNA sequences in vitro, the N-terminal WH1 domain of the plasmid DNA replication initiator RepA assembles as amyloid fibres. These are bundles of single or double twisted tubular filaments in which distorted RepA-WH1 monomers are the building blocks. When expressed in Escherichia coli, RepA-WH1 triggers the first synthetic amyloid proteinopathy in bacteria, recapitulating some of the features of mammalian prion diseases: it is vertically transmissible, albeit non-infectious, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 58 publications
2
60
0
Order By: Relevance
“…WH1(A31V)-mCh propagates as at least two amyloid strains (or variants) with distinct morphologies and degrees of cytotoxicity whose interconversion is modulated by the Hsp70 chaperone DnaK (Gasset-Rosa et al, 2014), resembling the phase transitions observed in proteins involved in human amyloidoses (Giraldo et al, 2016). In coherence with the ability of DNA to promote RepA-WH1 amyloidosis in vitro , in E. coli cells amyloid precursors assemble at the bacterial nucleoid (Moreno-del Álamo et al, 2015). Interestingly, a recent study reveals that the full length RepA protein, through its WH1 domain, assembles as a functional amyloid at the bacterial nucleoid to physically couple plasmid DNA replication origins, thus preventing premature re-initiation events (Molina-García et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…WH1(A31V)-mCh propagates as at least two amyloid strains (or variants) with distinct morphologies and degrees of cytotoxicity whose interconversion is modulated by the Hsp70 chaperone DnaK (Gasset-Rosa et al, 2014), resembling the phase transitions observed in proteins involved in human amyloidoses (Giraldo et al, 2016). In coherence with the ability of DNA to promote RepA-WH1 amyloidosis in vitro , in E. coli cells amyloid precursors assemble at the bacterial nucleoid (Moreno-del Álamo et al, 2015). Interestingly, a recent study reveals that the full length RepA protein, through its WH1 domain, assembles as a functional amyloid at the bacterial nucleoid to physically couple plasmid DNA replication origins, thus preventing premature re-initiation events (Molina-García et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To identify secondary structure, we utilized the RepA-WH1 amino acid sequence and the 13 CO, 13 Cα, 13 Cβ and 15 N chemical shifts values as input to perform conformational chemical shift analysis using the web server CSI 3.0 31 . The same data were employed to determine the major cis/trans conformational state of the X-Pro bonds using the program Promega 32 .…”
Section: Synthesis Of Repa-wh1 Operator Dsdna (Opsp)mentioning
confidence: 99%
“…Spectra were processed with Topspin (Bruker Biospin, Karlsruhe, Germany) or NMRPipe 33 and analyzed with SPARKY 34 and NMRView 35 . The backbone and side chain 1 H, 13 R 1rho values and { 1 H}-15 N NOE of RepA-WH1 uniformly labeled with 13 C and 15 N were acquired using the approach of Kay and co-workers 36 . The spectra in each experiment were recorded in an interleaved fashion.…”
Section: Synthesis Of Repa-wh1 Operator Dsdna (Opsp)mentioning
confidence: 99%
See 1 more Smart Citation
“…30 More recently, this group showed that this bacterial prionoid can seed amyloid aggregation of mutants from the same protein, 31 and characterized the bacterial nucleoid as the initial site of assemble of these prionlike aggregates. 32 This bacterial amyloidosis, shared some characteristics with mammalian prion diseases, mainly transmissibility and the presence of phenotypically distinct strains.…”
Section: Introductionmentioning
confidence: 99%